2018
DOI: 10.1186/s11671-018-2649-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nanomaterials and Nanotechnologies in Wastewater Treatment: a Bibliometric Analysis

Abstract: Nanomaterials and nanotechnologies (NNs) have been shaping the wastewater treatment process unprecedentedly. Bibliometric methods are regarded as an indispensable light to guide direction in scientific domain. The present study aims to investigate the role of NNs in wastewater treatment with bibliometric techniques based on SCI databases from 1997 to 2016. Results showed that China (962), USA (324) and Iran (140) are the most productive countries. Chinese Academy of Sciences (149), Tongji University (49), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 75 publications
2
38
0
Order By: Relevance
“…The length between the nodes in the network can reflect the relationship of the subject content, which in turn demonstrates the structural changes in the research field [46]. In order to objectively analyze the research hotspots of algal-bacterial symbiosis in wastewater treatment, CiteSpace, a kind of citation visualization software, was used to construct the scientific knowledge mapping from two aspects of burst detection and timezone view [47].…”
Section: Resultsmentioning
confidence: 99%
“…The length between the nodes in the network can reflect the relationship of the subject content, which in turn demonstrates the structural changes in the research field [46]. In order to objectively analyze the research hotspots of algal-bacterial symbiosis in wastewater treatment, CiteSpace, a kind of citation visualization software, was used to construct the scientific knowledge mapping from two aspects of burst detection and timezone view [47].…”
Section: Resultsmentioning
confidence: 99%
“…However, raw Kaol exhibit relatively low sorption capacity due to the low reactivity and specific surface area. Researchers have approved that nanomaterials and nanotechnologies have been shaping the wastewater treatment process unprecedentedly [ 11 14 ]. In order to increase the reactivity and specific surface area of Kaol, various methods such as organic modification, acid or alkaline activation, delamination, and exfoliation were developed [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other scientometric studies were developed about the following themes: (a) groundwater remediation research (Chen et al, 2019), (b) authorship pattern of rain water harvesting research management publications (Pu & Raja, 2019), and (c) the role of nanomaterials and nanotechnologies in wastewater treatment (Jiang et al, 2018). Chen et al (2019) studied groundwater research based on 2867 journal articles published from January 1950 to September 2018 from the Science Citation Index Expanded database with CiteSpace software.…”
Section: Other Scientometric Water Studiesmentioning
confidence: 99%
“…Finally, Pu & Raja (2019) concluded that three authors' collaboration was dominant during the period of study, that the author productivity was higher from 2008 to 2010, that the degree of collaboration was identified as the value 0.935, and that the study shows the increase of the trend towards the collaborative research. Jiang et al (2018)…”
Section: Other Scientometric Water Studiesmentioning
confidence: 99%